Analisis Penerapan Akuntansi Pertanggungjawaban Pada Grand Nanggroe Hotel di Aceh - Vidia Isma Ulya; Indayani Indayani; Riha Dedi Priantana (SAR (Soedirman Accounting Review) : Journal of Accounting and Business, 2021)
This study aims to analyze how responsibility accounting is applied to the Grand Nanggroe Hotel with 4 elements of responsibility accounting, namely responsibility assignment, performance measurement standards, performance evaluation and reward systems. This study uses primary data and secondary data with documentation and interview data collection methods. The data analysis technique used in this research is descriptive statistics.The results showed that Grand Nanggroe Hotel implemented a responsible accounting system, but the performance of Grand Nanggroe Hotel in general was still ineffective because there were still realizations that did not match the budget.